Congenital Nephrotic Syndrome, an Uncommon Presentation of Cytomegalovirus Infection - Rahman, H; Begum, A; Jahan, S; Muinuddin, G; Hossain, MM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):210-3.The abstract of this article is available on the PubMed website